Antioxidant, antimicrobial and antifungal activity of the obtained "Cachisept" tablets for resorption in the oral cavity for the treatment and prevention of dental caries - O. Yu. Maslov; M. A. Komisarenko; S. V. Ponomarenko; S. V. Kolisnyk; T. P. Osolodchenko; T. A. Kostina; Yu. S. Kolisnyk; V. P. Moroz (Zaporozhye State Medical University, 2023)
Dental caries stands as a highly common chronic ailment affecting individuals globally, with susceptibility to this condition spanning their entire lifespan. Consequently, the search for novel medications aimed at treating and preventing dental caries holds significant importance in the field of pharmacy. The aim of the work was to study the antioxidant, antimicrobial, and antifungal activity of the obtained oral tablets "Сaсhisept" for resorption in the oral cavity for the treatment and prevention of dental caries. Materials and methods. The obtained tablets "Сaсhisept" with green tea leaf extract were the object of investigation. Antioxidant activity was established by the potentiometric method, and antimicrobial and antifungal activity was assessed by the agar well diffusion method. Results. The level of antioxidant activity for tablets "Сaсhisept" was 110.00 ± 2.20 mmol-eqv./mdry res, the obtained tablets had a high level of antioxidant activity according to Maslov's conditional classification. Staphylococcus aureus (25.33 ± 0.50 mm), Baсillus subtilis (25.33 ± 0.50 mm) and Streptococcus mutans (25.33 ± 0.50 mm) were the most sensitive to the obtained "Сaсhisept" tablets, and the least - Proteus vulgaris (20.67 ± 0.50 mm), and it was observed strong growth inhibition in relation to the fungus Candida albicans (20.00 ± 0.50 mm). Conclusions. The presented study has found that "Сaсhisept" tablets have a high level of antioxidant activity, and also have a high antimicrobial and antifungal effect against all investigated Gram-positive, Gram-negative bacteria, and the Candida albicans fungus. Thus, "Сaсhisept" tablets can be recommended for the treatment and prevention of dental caries.